THE IMPACT OF ONLINE PRODUCT REVIEW ON YOUTUBE TOWARD PURCHASE INTENTION OF SMARTPHONE - Qori, Chubbiansyah; Aprilianty, Fitri (Journal of Business and Management, 2018)
Abstract. YouTube is one of the largest social media in the last 5 years. Website that provides the means of watching videos and users who can upload their own video is quite a lot of attention of the people of Indonesia. Became the third order as social media visited by Indonesian average as much as 14,5 billion people watch this every single day (APJII, Indonesia Internet User, 2016). One kind of video that is quite often seen is an online video review product. Online video review product is a kind of video that experience the buyer about some product. This research will discuss about how the effect of online video review on YouTube to purchase intention someone who has seen the video review. Some variables of video like quantity of post, views, likes, comment, and review, perceived risk, perceived credibility, and special attention toward YouTube itself will be the main focus in conceptual framework research. Statistic method to be used in this research is Pa rtial Least Regression (PLS) which will describe the relationships that exist on each variable. In conclusion after do some several phases in this research, researcher can answer the question of the research. In conclusion, this research find that variable in the conceptual framework have a significance effect on purchase intention of smartphone. This finding can be some way of marketers to get closer channel to target market especially give the information of the product.Keywords: Online Video Product, Partial Least Square, Purchase Intention, User Generated Content ,YouTubeÂ